Internationalization as a way to leverage small and medium management consulting companies: case study of winning management consulting internationalizing opportunities in Italy, Spain and United Kingdom - Ferreira, Iolanda Paulino (2015)
The management consulting industry represents a niche of the consulting market that have been growing at a faster rate during the last decade. This rapidity of grow led to an increase of the market competition among specialized SME’s and to the need to look for new markets outdoors in order to keep growing. The decision of whether the firm should internationalize for that or other country is a strategic decision that cannot be made without balancing all the external influences presents in that market. Due to this fact, this dissertation was made with the objective of measuring the attractiveness of a foreign management consulting markets for Portuguese management consulting SME’s and how that external influences can affect the performance of the company that is internationalizing. This dissertation focus is Winning Management Consulting, a Portuguese management consulting start-up that started its operations in the end of 2011 and intends to expand its business for the Italian, Spanish and United Kingdom markets which attractiveness analyses will determine whether it is a good option or not.